Obstructive acute abdomen by metastatic malignant melanoma: case report - Ros, Carlos Teodósio Da (2022)
We relate a case of a patient with acute intestinal obstruction due of a malignant metastatic melanoma. Two years ago, the patient underwent to resection of one dorsal malignant melanoma. It is an infrequent neoplasm, and more rare is the place of this metastasis.